Forage and grain production of dual-purpose wheat under different sowing densities, nitrogen fertilizer levels and cuts managements (Revista de Ciências Agroveterinárias, 2018)
The aim of this study was to evaluate the forage yield and grain productivity of dual-purpose wheat under different nitrogen fertilizer levels, harvesting managements and sowing densities. The experimental design was a completely randomized with four repetitions and had a factorial treatment arrangement (sowing density vs. nitrogen level) with sub-parcels (harvesting management). The sowing densities were 400 and 500 viables seed m-2. Nitrogen levels were 100, 150, 200, 250 and 300% of recommended levels, applied on the base during tillering and after each harvest. The split-plot-parcels were divided according to harvesting management (zero, one and two cuts). Two consecutive cuts provided greater forage accumulation, without affect mineral composition, crude protein content and productivity. Nitrogen fertilizer level must be 2.5 times higher for two harvest level, because increase forage yield. The greater sowing density increased grain productivity but did not affect forage yield in second harvest. The treatments did not change crude protein content.
Keywords: Triticum aestivum; grain yield; biomass; Triticum; regimes production